Model Manajemen Pembelajaran Pendidikan Islam Berbasis Masalah: Studi Kasus pada Jurusan Tarbiyah dan Adab IAIN Parepare - Sewang, Anwar; Halik, Abdul (JPPI (Jurnal Pendidikan Islam Pendekatan Interdisipliner), 2019)
Learning in college is very urgent considering aspects of relevance and effectiveness. One strategy that becomes the trend of study is problem-based learning. Problem-based learning strategies are considered urgent and relevant to be applied in higher education, as an effort to trigger scientific exploration to foster critical and creative thinking skills. Problem based learning strategies should be based on research in order to have a systemic scientific structure, a strong, functional and implementative foundation in learning. The relevance and effectiveness of the implementation of problem-based learning strategies is designed with a management approach. Management breaks down the stages of problem-based learning strategies, including planning, implementation, and evaluation (assessment). Problem-based learning strategy planning includes the preparation of Semester Learning Plans (Rencana Pembelajaran Semester or RPS) that refer to the curriculum of study programs, establish learning outcomes, design teaching materials, analyze students, choose media, compile learning evaluation systems, and predict possible problems. All of them are designed with problem-based adapted from the results of the research. Implementation of problem-based learning begins with initial activities including attendance, apperception, orientation, and motivation, core activities include exploration, elaboration, and confirmation, and final activities including conclusions and assessments (evaluations). Evaluation of learning includes program assessment, implementation assessment, and assessment of goals achievement. Principles of learning assessment include educative, objective, accountability, and transparent. Measuring the achievement of problem-based learning is seen in indicators of critical and creative thinking abilities, including problem response, understanding problems, knowing cause of problems, able to find alternative solutions, recognize the impact of the problem, and be able to connect with other science disciplines. The strategy of problem-based learning in higher education has implications for students' interest and motivation in developing critical and creative thinking skills.